2020
DOI: 10.1111/jpm.12686
|View full text |Cite
|
Sign up to set email alerts
|

Mental health nurses’ perceived preparedness to work with adults who have child sexual abuse histories

Abstract: Accessible summary What is known on the subject? The high prevalence of adults presenting to the mental health services places mental health nurses (MHNs) in a unique position to help to identify and support the person with the associated challenges of child sexual abuse (CSA). Feelings of discomfort have been identified by mental health nurses (MHNs) when working with survivors of CSA due to a lack of knowledge, poor confidence and feeling unprepared to inquire and respond to such a sensitive topic. What … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Supplementary Document S2 is a complete list of all included articles. Studies excluded at full-text screening (n = 27) [ 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 ] are listed in Supplementary Document S3 . Data extracted from included studies are summarised in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Supplementary Document S2 is a complete list of all included articles. Studies excluded at full-text screening (n = 27) [ 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 ] are listed in Supplementary Document S3 . Data extracted from included studies are summarised in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Over the past 25 years, research has identified numerous reasons as to why practitioners are reticent to address CSA in those presenting with mental health problems. Reasons for reticence are complex, but include lack of knowledge; low level of interpersonal skills, discomfort in asking about and addressing disclosure of sexual abuse; fear of retraumatization, time and resource constraints; adherence to the medical model, beliefs and attitudes regarding sexual abuse and its place in relation to mental health problems; believing CSA is the concern of 'other' specialists, and a practitioner's own experiences with CSA (Kennedy et al 2021;Stige et al 2022;Walsh et al 2022;Warne & McAndrew 2005). These barriers perpetuate CSA not being addressed at all.…”
Section: Discussionmentioning
confidence: 99%
“…However, over a prolonged period, mental health professionals, such as nurses and psychiatrists, have been disinclined to routinely enquire about sexual abuse histories for numerous reasons; lack of confidence in how to ask and effectively respond, poor understanding and knowledge of CSA, and fear of reopening traumatic experiences (Dorahy & Clearwater 2012;Walsh et al 2022). Practitioners' avoidance of addressing CSA appears common throughout mental health care, including Child and Adolescent Mental Health Services (CAMHS) and male and female acute services (Kennedy et al 2021;Stige et al 2022;Walsh et al 2022;Warne & McAndrew 2005). Such lack of professional preparedness and/or willingness to address CSA could add to the distress and compromise the recovery of those they are providing care for.…”
Section: Csa and Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, not only (TIC) training increases psychiatric nurses’ comfort, knowledge and screening confidence (Kalmakis et al . 2018), which are needed to support and maintain the well‐being of mental health nurses in clinical practice (Kennedy et al 2020), but also heighten their empathy on understanding their patients’ background (Kia‐Keating et al . 2019).…”
Section: Relevance For Nursing Practicementioning
confidence: 99%